Inhibitory Effects of Myricetin on Lipopolysaccharide-Induced Neuroinflammation - Jung-Hee Jang; Seung Hoon Lee; Kyungsook Jung; Horyong Yoo; Gunhyuk Park (Brain Sciences, 2020)
Microglial activation elicits an immune response by producing proinflammatory modulators and cytokines that cause neurodegeneration. Therefore, a plausible strategy to prevent neurodegeneration is to inhibit neuroinflammation caused by microglial activation. Myricetin, a natural flavanol, induces neuroprotective effects by inhibiting inflammation and oxidative stress. However, whether myricetin inhibits lipopolysaccharide (LPS)-induced neuroinflammation in hippocampus and cortex regions is not known. To test this, we examined the effects of myricetin on LPS-induced neuroinflammation in a microglial BV2 cell line. We found that myricetin significantly downregulated several markers of the neuroinflammatory response in LPS-induced activated microglia, including inducible nitric oxide (NO) synthase (iNOS), cyclooxygenase-2 (COX-2), and proinflammatory modulators and cytokines such as prostaglandin E2 (PGE2), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α). Moreover, myricetin suppressed the expression of c-Jun NH2-terminal kinase (JNK), p38 MAPK, and extracellular signal-regulated kinase (ERK), which are components of the mitogen-activated protein kinase (MAPK) signaling pathway. Furthermore, myricetin inhibited LPS-induced macrophages and microglial activation in the hippocampus and cortex of mice. Based on our results, we suggest that myricetin inhibits neuroinflammation in BV2 microglia by inhibiting the MAPK signaling pathway and the production of proinflammatory modulators and cytokines. Therefore, this could potentially be used for the treatment of neuroinflammatory diseases.